Comparison of the Effectiveness of the Core Stabilization Exercise Model and the Schroth Method in Treating Balance Disorders in Adolescents with Idiopathic Scoliosis (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Poor posture habits can cause several postural defects, one of which is idiopathic scoliosis. Scoliosis is a postural disorder caused by changes in the shape and function of muscles and bones in the vertebrae, characterized by an abnormal curvature of the spine to the left and right. This can cause poor posture, balance disorders, and functional disabilities, increasing the risk of permanent disability. The research method used was a quasi-experimental design with a pre-test and post-test with a control group design, where the subjects were divided into three groups: experimental group 1 (given core stabilization exercises), experimental group 2 (given the Schroth method), and the control group (given no intervention or only given conventional therapy). The sample used was 32 students of SMK 1 Muhammadiyah 1 Pekanbaru. The purpose of this study was to compare the effectiveness of each intervention method separately on improving postural balance in adolescents with idiopathic scoliosis. The results of this study were that the Schroth method was more effective for balance than the core stabilization exercise method.